Test The Effect of The Inhibitory Power and Minimum Killing Power of Clove Flower Oil (Syzigum aromaticum) with Water as a Solvent Against Staphylococcus aureus - Putra, Hendra Susana; Mahrus; Sedijani, Prapti; Al Idrus, Agil; Zulkifli, Lalu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Excessive use of antibiotics in treating infectious diseases has caused some bacteria to become resistant. Therefore, it is hoped that the use of natural ingredients such as cloves can be an alternative solution in reducing excessive use of antibiotics. This study aims to test the inhibitory effect and minimum killing power of clove flower oil (Aromatic syzygum) with water as a solvent against Staphylococcus aureus. In determining the inhibition zone, the diffusion disk method was used. Meanwhile, determining the Minimum Kill Ability (MKA) uses the liquid tube dilution method. The results showed that an increase in the concentration of clove flower extract was followed by an increase in the inhibition zone in the media with the isolate Staphylococcus aureus. Meanwhile, in measuring the Minimum Kill Ability, the results showed that the MKA value of clove leaf extract against bacteria Staphylococcus aureus smaller than 5%. This shows that only a 5% concentration of clove leaf extract is enough to inhibit growth Staphylococcus aureus. These findings indicate the potential of clove leaf extract as an antimicrobial agent for bacteria Staphylococcus aureus. So it is hoped that natural ingredients will be able to reduce excessive use of antibiotics.